PENERAPAN MEDIA BELAJAR ALAT PERAGA DADU PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS II SDN 35 KAMPUNG SAWAH KABUPATEN PESISIR SELATAN - Irmawati Irmawati (JRTI (Jurnal Riset Tindakan Indonesia), 2016)
Rapidly global enhancement requires human having intellectual, active, and cooperative skill. These things are learning achievement that can be obtained through education field. In order to gain the purpose, teacher is required to give inovations in teaching. One of them is by using appropriate learning media. In this research, visual aid of dice was applied in mathematics subject to improve the learning achievement of student grade II SDN 35 Kampung Sawah Kabupaten Pesisir Selatan. This research was aimed to improve students’ learning achievement including learning outcome, activity, and cooperative skill. This research consists of two cycles with one meeting for each cycle. Analyzed data are obtained from result of observation and evaluation. Based on the research result, it can be concluded that: (1) students’ learning outcomes are inproved significantly; (2) students’ learning activities incline to increase; (3) students’ cooperative skill during learning process appear and show increasement.